Ablation Therapy for Persistent Atrial Fibrillation - Ifedili, Ikechukwu; Mouksian, Kristina; Jones, David; El Masri, Ibrahim; Heckle, Mark; Jefferies, John; Levine, Yehoshua C. (Current Cardiology Reviews, 2022)
Atrial Fibrillation (AF) is the most common form of electrical disturbance of the heart and contributes to significant patient morbidity and mortality. With a better understanding of the mechanisms of atrial fibrillation and improvements in mapping and ablation technologies, ablation has become a preferred therapy for patients with symptomatic AF. Pulmonary Vein Isolation (PVI) is the cornerstone for AF ablation therapy, but particularly in patients with AF occurring for longer than 7 days (persistent AF), identifying clinically significant nonpulmonary vein targets and achieving durability of ablation lesions remains an important challenge.
Keywords: cryoballoon